1996
DOI: 10.1507/endocrj.43.657
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in Serum Levels of Thyroid Hormone in Patients with Coronary Heart Disease.

Abstract: Abstract. The aim of this study was to evaluate the relationship between subclinical hypothyroidism and/or autoimmune thyroid disease and coronary heart disease (CHD). Ninety seven patients diagnosed as having CHD by a coronary angiography (CHD group) and 103 healthy subjects matched for age, sex and body mass index (control group) were included in the study. Thyroid function, thyroid autoantibodies and serum lipid concentrations were measured in the CHD and control groups. The CHD group exhibited significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
33
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 29 publications
2
33
1
Order By: Relevance
“…Our findings are at least in part in line with previous studies that found an association between hypothyroidism and an elevated risk for coronary artery disease in both males and females [9,10]. In contrast, certain cross-sectional studies could not confirm an association of hypothyroid function and atherosclerosis [19][20][21].…”
Section: Discussionsupporting
confidence: 91%
“…Our findings are at least in part in line with previous studies that found an association between hypothyroidism and an elevated risk for coronary artery disease in both males and females [9,10]. In contrast, certain cross-sectional studies could not confirm an association of hypothyroid function and atherosclerosis [19][20][21].…”
Section: Discussionsupporting
confidence: 91%
“…In addition, some studies have demonstrated an association between thyroid autoimmunity and coronary heart disease in (subclinical) hypothyroidism (35-37), while we did not find any association between TPO antibody positivity itself, carotid plaque formation and serum TSH levels in any direction. For low TSH values, this is in line with a previous study that could not confirm an association between thyroid antibodies and atherosclerosis in hypothyroid subjects (5,38,39). Regarding the association of low serum TSH levels, carotid plaque formation, and prevalent stroke, the interpretation is much more complex.…”
Section: Discussionsupporting
confidence: 85%
“…Studies on the relationship between normal range of thyroid function and CAD had produced inconsistent results [10][11][12][13][14][15]. The discrepancies might derive from the number of enrollment, heterogenous subjects and racial difference et al However, the effect of age on this relationship was neglected and none of them performed an age-stratified analysis.…”
Section: Discussionmentioning
confidence: 99%
“…One prospective study indicated TSH levels within the reference range were positively and linearly associated with cardiovascular mortality in women [9] and four cross-sectional studies [10][11][12][13] reported that relatively low thyroid function within the reference range was associated with the presence of CAD, while two others [14][15] did not confirm these findings. These results arouse the debate on whether there is a need to redefine the upper normal limit of TSH [16][17].…”
mentioning
confidence: 99%